Holiday town - Dall, Nicholas (Department of English Language and Literature, 2024)
On a windless day in the holiday season Betty's Bay is often seen as more than a sum of its parts. Its name seems fitting, and only a little trite. The beach is white and the sea is blue. If you go out beyond the breakers and float on your back you can see only the mountains. In the holiday season the locals melt into the landscape. They become nothing more than shop assistants and waitresses. There are coffee shops and art galleries in Betty's Bay, restaurants and a confectioner. There is a beach with warmer water than the beaches in Cape Town and there is the Harold Porter Botanical Garden. There are three lakes in Betty's Bay.